Catholic Church and education in Peru: A quantitative analysis - Chávez Contreras, Germán (2008)
This work offers a statistical analysis that quantifies the educational work of the Catholic Church in Peru today. With recent statistics, the study reveals how Catholic education has contributed effectively and extensively, throughout the national territory, to the action of the Peruvian State, allowing a better understanding of the importance of its presence in civil society for the common good.